2005
DOI: 10.1103/physrevlett.94.174301
|View full text |Cite
|
Sign up to set email alerts
|

Second Mode of Recycling together with Period Doubling Links Single-Bubble and Multibubble Sonoluminescence

Abstract: We report the existence of a second type of recycling mode that occurs for air-seeded bubbles. Observation of period doubling in both the stable, the first type, and the second type of recycling mode, together with simultaneous measurement of the relative phase of light emission compared to the drive, shows that the instability boundaries of period doubling and bubble extinction are mainly determined by the bubble size irregardless of the gas composition. The second type mode seems to represent a link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Taking into account the characteristics of the recycling mode, specifically, the existence of a period doubling in SL amplitude and correlated spatial anisotropy, 11 and the pinch off of the bubble in fragments, 10,11 we associated the onset of this phenomenon to a nonspherical acoustic pressure perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking into account the characteristics of the recycling mode, specifically, the existence of a period doubling in SL amplitude and correlated spatial anisotropy, 11 and the pinch off of the bubble in fragments, 10,11 we associated the onset of this phenomenon to a nonspherical acoustic pressure perturbation.…”
Section: Discussionmentioning
confidence: 99%
“…In type 2, instead, the instability threshold is reached before the burn off becomes efficient and, therefore, the bubble is mostly air filled. 10 Dam and Levinsen 10 observed that both types of recycling modes are preceded by a period doubling in the amplitude of SL. This fact and the spatial anisotropy in the flashes are indications that the instability would be instigated by a nonspherical perturbation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In [105][106][107][108], a spatial anisotropy of radiation was observed. The authors believe that the effect is caused by the instability of the bubble shape, namely, its devi ation from a spherical shape at the last stage of col lapse.…”
Section: Size Of Source: Anisotropy Of Radiationmentioning
confidence: 98%